A study into the right to existence of cults in Malaysia / Danial Amir, Farah Najiha Md. Radi and Rijalul Fauzi Mustapa - Amir, Danial; Md. Radi, Farah Najiha; Mustapa, Rijalul Fauzi (2006)
Freedom of religion granted by the Federal Constitution has been thrown into the limelight in recent times, especially after the persecution of cultist groups like the Black Metal cults, Sky Kingdom, and the Al Maunah. As unconstitutional as this may seem, there exist certain provisions within the Constitution, the Penal Code and the Syariah Criminal Enactments that allows for the freedom of religion to be abridged. This research will delve into these provisions to ascertain the answer to what constitutes a religious act worthy of executive reprimand, taking the Black Metal cults, the Jehovah Witnesses, Tarekat Mufariidiah, Qadiani, Al Arqam and the Al Maunah groups as the main subjects of research. The research will also delve into the issues of the public, and how sentiments therein may affect a cult's right to existence. This research is of paramount importance as it attempts to synchronise the multiple laws that exist regarding religion into one coherent compilation to allow for clarity in answering that question of questions; do cults have the right to exist in Malaysia.